Necrotizing enterocolitis totalis complicates an infantile presentation of ARL6IP1-related spastic paraplegia 61 - E.K. Ninmer; M.C. Spaeder; C.M. Peroutka; D.E. Levin (Elsevier, 2021)
Spastic paraplegia 61 is a rare, complicated form of hereditary spastic paraplegia characterized by diffuse sensory and motor polyneuropathy. Knowledge about the clinical manifestations of disease in patients with this genetic condition is limited. We describe a case of a 4-month-old infant with spastic paraplegia 61 (SPG61) who developed severe bowel inflammation consistent with necrotizing enterocolitis totalis. To our knowledge, this is the first reported case of necrotizing enterocolitis in a patient with this genetic condition.